Anti-diabetic drugs and weight loss in patients with type 2 diabetes. (September 2021) - Lazzaroni, Elisa; Ben Nasr, Moufida; Loretelli, Cristian; Pastore, Ida; Plebani, Laura; Lunati, Maria Elena; Vallone, Luciana; Bolla, Andrea Mario; Rossi, Antonio; Montefusco, Laura; Ippolito, Elio; Berra, Cesare; et al.
Abstract: Introduction: Obesity is frequently a comorbidity of type 2 diabetes. Even modest weight loss can significantly improve glucose homeostasis and lessen cardiometabolic risk factors in patients with type 2 diabetes, but lifestyle‐based weight loss strategies are not long‐term effective. There is an increasing need to consider pharmacological approaches to assist weight loss in the so called diabesity syndrome. Aim of this review is to analyze the weight-loss effect of non-insulin glucose lowering drugs in patients with type 2 diabetes. Material and methods: A systematic analysis of the literature on the effect of non-insulin glucose lowering drugs on weight loss in patients with type 2 diabetes was performed. For each class of drugs, the following parameters were analyzed: kilograms lost on average, effect on body mass index and body composition. Results: Our results suggested that anti-diabetic drugs can be stratified into 3 groups based on their efficacy in weight loss: metformin, acarbose, empagliflozin and exenatide resulted in a in a mild weight loss (less than 3.2% of initial weight); canagliflozin, ertugliflozin, dapagliflozin and dulaglutide induces a moderate weight loss (between 3.2% and 5%); liraglutide, semaglutide and tirzepatide resulted in a strong weight loss (greater than 5%). Conclusions: This study shows that new anti-diabetic drugs, particularly GLP1-RA and Tirzepatide, are the most effective in inducing weight loss in patients with type 2 diabetes. Interestingly, exenatide appears to be the only GLP1-RA that induces a mild weight loss. Graphical Abstract: ga1